2018
DOI: 10.1590/1678-98652018000200001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and hypocholesterolemic effect of milk kefir and water kefir in Wistar rats

Abstract: A B S T R A C T ObjectiveTo compare the effects of fermented kefir on the nutritional, physiological, and biochemical parameters of rats. MethodsGrains of milk kefir (whole and skimmed) and water kefir (brown sugar) were used. The chemical composition analysis was performed on substrates and fermented beverages. The rats were evaluated for weight gain, body CC BY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 29 publications
(32 reference statements)
1
17
0
6
Order By: Relevance
“…Fermentation time had a significant effect on water content but there was no significant difference between green coconut water kefir of treatments T1, T2 and T3. Magalhães-Guedes et al (2010) and Rocha-Gomes et al (2018) also found similar results in Brazilian sugary water kefir and brown sugar water kefir within a range of 95-98%. The high water content of kefir in the current study was also caused by the largest component of the medium which consists of 95% water (Yong et al, 2009), hence the name water kefir.…”
Section: Water Contentsupporting
confidence: 67%
See 1 more Smart Citation
“…Fermentation time had a significant effect on water content but there was no significant difference between green coconut water kefir of treatments T1, T2 and T3. Magalhães-Guedes et al (2010) and Rocha-Gomes et al (2018) also found similar results in Brazilian sugary water kefir and brown sugar water kefir within a range of 95-98%. The high water content of kefir in the current study was also caused by the largest component of the medium which consists of 95% water (Yong et al, 2009), hence the name water kefir.…”
Section: Water Contentsupporting
confidence: 67%
“…Protein content of samples throughout the fermentation period ranged between 4.05% and 6.04%. These results were higher than the protein content of Brazilian sugary water kefir fermented for 24 hours which was 0.4% (Magalhães-Guedes et al, 2010) and brown sugar water kefir which was 0.27% after 48 hours fermentation (Rocha-Gomes et al, 2018). The protein content of a fermented product usually increases with fermentation time due to the increase of microbial biomass and secretion of protein molecules (Magalhães-Guedes et al, 2011).…”
Section: Protein Contentmentioning
confidence: 95%
“…In the present study, the cafeteria-fed animals showed dyslipidemia in the blood evaluation, with an increase in LDL-c, VLDL-c and triglycerides serum levels. The LDL fraction is synthesized in the liver, and its main function is to carry cholesterol to peripheral tissues, while HDL-c performs the reverse transport of cholesterol, taking it from tissues to the liver (Rocha-Gomes et al, 2018;Stols-Gonçalves et al, 2019). Therefore, the increase in LDL-c in the cafeteria group indicates an accumulation of fat in the liver, in an attempt to carry the lipids of the diet lodged in the liver into the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…About 1 mL of blood serum was collected to determine the total cholesterol, high density lipoprotein (HDL-c), glucose, triglycerides, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) according to the protocol set forth by the kits manufacturer (Labtest V R ). The low density lipoprotein (LDL-c) and very low density lipoprotein (VLDL-c) were calculated as described by Rocha-Gomes et al(2018). Additionally, fecal and hepatic Hepatic steatosis and redox imbalance cholesterol and triglycerides levels were determined as described by Escobar et al (2019).…”
Section: Hepatic Evaluationsmentioning
confidence: 99%
“…The animals were weighed weekly, and weight gain was calculated by subtracting from the weight obtained on the last day of the experiment, the initial weight. The food and energy efficiency of each diet was calculated by the ratio of weight gain on total food and on total energy intake, respectively (Rocha-Gomes et al, 2018). Notes: Chow (Nuvilab V R CRÀ1); Chow þ Lard (20% w/w; Sadia V R ); Chow þ Olive oil (20% w/w; Gallo V R ); Chow þ Lard (10% w/w; Sadia V R ) þ Olive oil (10% w/w; Gallo V R ).…”
Section: Nutritional Assessmentmentioning
confidence: 99%